Empowering Students' English Communication Skills Through Participatory Learning in Pesantren - Istiqomah Nur Rahmawati; Nur Syamsiah; Rohmatillah; Nor Rochmatul Wachidah (TAAWUN, 2025)
This community service program aimed to enhance the English-speaking skills of students at Pondok Pesantren Tahfidzul Qur’an Al-Quds in Bandar Lampung through a Participatory Action Research (PAR) approach. Implemented over three months in three action cycles: Look, Think, and Act, the program involved students and pesantren administrators in all phases of contextual, theme-based learning drawn from students’ daily activities such as prayer routines, dormitory interactions, and Islamic value discussions. Evaluation results revealed a 17.2-point average increase between pre-test and post-test scores, alongside affective improvements such as confidence and active participation. Interviews and reflection sessions indicated tangible benefits, including the emergence of peer mentors and an engaging learning atmosphere. These findings affirm that integrating participatory methods with religious and contextual content meaningfully supports students’ speaking skill development in pesantren settings.